HIGHER EDUCATION AND SCIENCE IN THE REPUBLIC OF ALBANIA: COOPERATION WITH THE FRENCH REPUBLIC, STATE AND PЕRSPECTIVES - Topalović, Milica (Serbian political thought, 2023)
The work covers a wide field of origin, and development, but also the current state of higher education and science in the Republic of Albania. In all post-communist countries, higher education is a mirror of the entire society and the political-economic state of the country, and in Albania, too, a long evolutionary process of turmoil between conservative and more liberal higher education policies can be observed, which resulted in a decline in the quality of education and scientific research. On this path of harmonization with world and European standards in the field of higher education and science, the paper investigates the role of the French Republic, which gives rise to the research question: At what level are the bilateral relations between the Republic of Albania and the French Republic in the field of higher education and science, bearing in mind that is the Republic of Albania a permanent member of the francophone organization, as well as the fact that the share of the Albanian francophone population is significant? The work will especially take into account the mobility of Albanian students, programs, and projects implemented at Albanian universities with the help of the Government of France, universities, cities and regions, and private companies, but will also include the problems of excessive outflow of the educated and able-bodied population. The author's conclusion is that the presence of France is not negligible, but still insufficient considering the traditionally friendly relations of these two countries. Of particular importance will be the use of the method of document analysis, genealogy, as well as analytical-descriptive methods.
Keywords: Republic of Albania; higher education; science research; French Republic